Molecular and biological characterization of Streptococcus pneumoniae isolates from patients with pneumococcal meningitis - Aida N. Chagaryan; Natali V. Ivanchik; Alexey Yu. Kuzmenkov; Roman S. Kozlov; Irina I. Gaponova; Konstantin O. Mironov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2025)
The aim of the study is to provide key characteristics of Streptococcus pneumoniae isolates circulating in Russia in 2015–2020 and isolated from pneumococcal meningitis patients based on high-throughput sequencing data, including global pneumococcal sequence clusters, serotypes, virulence factors and genetic determinants of resistance, in comparison with clinical data on antimicrobial susceptibility.